2012
DOI: 10.1111/j.1467-789x.2012.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of clinical trials of the effects of low carbohydrate diets on cardiovascular risk factors

Abstract: A systematic review and meta-analysis were carried out to study the effects of low-carbohydrate diet (LCD) on weight loss and cardiovascular risk factors (search performed on PubMed, Cochrane Central Register of Controlled Trials and Scopus databases). A total of 23 reports, corresponding to 17 clinical investigations, were identified as meeting the pre-specified criteria. Meta-analysis carried out on data obtained in 1,141 obese patients, showed the LCD to be associated with significant decreases in body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
184
2
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(227 citation statements)
references
References 74 publications
10
184
2
14
Order By: Relevance
“…Low-glycaemic-index and low-glycaemic-load diets reduce fasting insulin and C-reactive protein levels, which might (to some extent) prevent the development of type 2 diabetes or ameliorate the habitual low-grade inflammatory state associated with obesity. 63 These metaanalyses 64,65 as well as other systematic reviews 41,66 could not prove additional beneficial or deleterious long-term effects associated with adherence to high-fat or high-protein diets.…”
Section: Meta-analysis and Systematic Reviewsmentioning
confidence: 98%
“…Low-glycaemic-index and low-glycaemic-load diets reduce fasting insulin and C-reactive protein levels, which might (to some extent) prevent the development of type 2 diabetes or ameliorate the habitual low-grade inflammatory state associated with obesity. 63 These metaanalyses 64,65 as well as other systematic reviews 41,66 could not prove additional beneficial or deleterious long-term effects associated with adherence to high-fat or high-protein diets.…”
Section: Meta-analysis and Systematic Reviewsmentioning
confidence: 98%
“…[5][6][7] Moreover, recently conducted meta-analyses of longterm trials show lasting effects after the cessation of active intervention. 8,9 Another meta-analysis has demonstrated benefits of a low glycaemic index diet among individuals with obesity.…”
Section: Correspondencementioning
confidence: 99%
“…A recent meta-analysis with low-carbohydrate/high protein diets has shown that such diets have benefit effects on weight loss, metabolic parameters and cardiovascular risk factors [9]. As far as we know, no interventional designs have been realized in order to evaluate the effect of this polymorphism on response to diets of this type.…”
Section: Introductionmentioning
confidence: 99%